Diseño y construcción de un prototipo de cuadricóptero para aplicaciones de adquisición de imágenes aéreas - Rujel Rubio, Wilfredo Cesar Richard (2019)
The present work consists of the design and construction of a quadcopter prototype for aerial image applications; This type of unmanned aircraft can be used in different applications of videos and aerial photographs, monitoring and surveillance of perimeter security, search and rescue support in inaccessible areas, monitoring of agricultural areas, monitoring of routes and roads, early warning and control of fires, among many more. It is required that the quadcopter can stay in flight for at least 15 minutes and, through a control system, remain stable in the air and in the position required for the capture of images. The main motivation for the development of this work is due to the technological boom that currently exists worldwide in this area of robotics and which seeks to implement a low-cost unmanned aerial vehicle capable of capturing images through a design methodology, this will serve as a base platform for future projects for the different areas of application that will improve the technological development of the region. For the development of this research project, a model of the base structure for the assembly for all the other components was proposed, for which a light and resistant material was selected for a basic structure of quadcopter. For the design of the electronic system, a flight controller card was selected with the technical characteristics capable of controlling the sensors and motors of the quadcopter and a basic control system based on PID that is responsible for keeping it stable in flight in a certain position. Finally, a wireless communication system was developed between a user interface and the quadcopter, which serves to send the flight coordinates and to receive the real-time images taken by the quadcopter.